Willingness to pay for social health insurance in Ethiopia: A systematic review and meta-analysis - Bayked, Ewunetie Mekashaw; Toleha, Husien Nurahmed; Chekole, Beletu Berihun; Workneh, Birhanu Demeke; Kahissay, Mesfin Haile (Frontiers in Public Health, 2023)
Background: Ethiopia plans to introduce social health insurance with the aim of giving recipients high-quality, long-term universal health care. It was anticipated to be fully operational in 2014. However, due to strong opposition from public employees, the implementation has been delayed multiple times. As a result, more and more studies have been conducted to collect evidence about the issue. However, there is no national pooled evidence regarding the willingness to pay for SHI. Thus, this review aimed to evaluate the willingness to pay for social health insurance and associated factors in Ethiopia. Methods: On September 1, 2022, database searches were conducted on Scopus, Hinari, PubMed, Google Scholar, and Semantic Scholar. Based on this search, 19 studies were included in the review. The risk of bias for the included studies was assessed using Joana Briggs Institute checklists. The data were extracted using Microsoft Excel. RevMan-5 was used to conduct the meta-analysis. The effect estimates assessed were the odds ratios at a p-value less than 0.05 with a 95% CI using the random effect model. Results: The pooled willingness to pay for social health insurance was 42.25% and was found to be affected by sociodemographic, health and illness status, health service related factors, awareness or knowledge level, perception or attitude towards the scheme, and factors related to the scheme. The pooled result showed that the willingness of participants to pay for the scheme was 16% less likely (OR = 0.84; 95% CI: 0.52-1.36). When the outlier was unchecked, the willingness to pay became 42% less likely (OR = 0.58; 95% CI: 0.37-0.91). The lowest willingness to pay for the scheme was in the Oromia region, while the highest was in Harar. Professionally, teachers were 3.22 times more likely to pay for the scheme (OR = 3.22; 95% CI: 1.80-5.76) than health professionals. Conclusion: The willingness to pay for social health insurance was low, less than 50%, particularly among health professionals, which urges the Ethiopian health insurance services to deeply look into the issue.